HGH1 Promotes Breast Cancer Progression Through the PI3K/AKT/NF-κB Signaling Pathway: Potential Role for Prognosis and Targeted Therapy - Hu W; Si D; Liu C; Tie D; Xu D; Li N (Breast Cancer: Targets and Therapy)
Wenyu Hu,1,* Dikun Si,1,* Chenxi Liu,2,* Danchen Tie,1 Dongdong Xu,1 Nanlin Li1 1Department of Thyroid, Breast and Vascular Surgery, Xijing Hospital, Air Force Medical University, Xi’an, Shaanxi, People’s Republic of China; 2Department of Obstetrics and Gynecology, The Second Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Nanlin Li, Email nanlin-74@163.comIntroduction: Previous studies have shown that the HGH1 gene is associated with poor prognosis in a variety of cancers, but its specific function and molecular mechanism in the pathological process of breast cancer remain unclear.Methods: The relationship between expression of HGH1 and overall survival in BC patients was analyzed. Enrichment analysis of HGH1-related signaling pathways and immune infiltration was performed. BC cell lines with overexpression and knockdown of HGH1 gene were constructed to tested the proliferation, migration, invasion ability and cell apoptosis. Detected the expression of PI3K/AKT pathway in BC cells and treated it with PI3K inhibitor. The effect of HGH1 on breast cancer in vivo was observed by tumor xenograft experiment.Results: The expression of HGH1 is significantly increased in breast cancer and related to poor prognosis. The high expression of HGH1 is related to the PI3K−Akt signaling pathway, cell cycle, cell senescence, P53 signaling pathway. Overexpression of HGH1 promotes the proliferation, migration, and invasion, and inhibits apoptosis, while its knockdown yields opposite effects. HGH1 promoted the growth of BC cells by activating the PI3K/AKT/NF-κB signaling pathway, and the use of PI3K inhibitors could attenuate the promoting effect. In vivo experiments confirmed that HGH1 promoted breast cancer growth.Conclusion: HGH1 promotes the growth of BC cells by activating the PI3K/AKT/NF-κB signaling pathway. HGH1 may become a new indicator for evaluating the poor prognosis of BC patients and serve as a potential diagnostic biomarker and therapeutic target for breast cancer.Keywords: breast cancer, HGH1, PI3K, circadian